2014
DOI: 10.1111/hcre.12029
|View full text |Cite
|
Sign up to set email alerts
|

Linking Emotion to the Conflict Face-Negotiation Theory: A U.S.-China Investigation of the Mediating Effects of Anger, Compassion, and Guilt in Interpersonal Conflict

Abstract: This study linked emotion to the theoretical assumptions of the face‐negotiation theory and probed the critical role of anger, compassion, and guilt in understanding the complex pathways of their relationships with self‐construal, face concerns, and conflict styles in U.S. and Chinese cultures. Results showed that anger was associated positively with independent self‐construal, self‐face concern, and the competing style, and compassion was associated positively with interdependent self‐construal, other‐face co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 47 publications
2
42
0
2
Order By: Relevance
“…In support to this notion, the recognition of basic features (i.e., perceptual) carrying primary emotional information has been considered a fast and automatic process (Pratto and John, 1991; Öhman et al, 2001) responsible for programing and executing social responses (Fazio and Olson, 2003). This view has emerged from the use of experimental tasks designed to evaluate emotion recognition of faces (Heuer et al, 2007; Hurtado et al, 2009; Luo et al, 2010; Ibáñez et al, 2011, 2014; Petroni et al, 2011; Zhang et al, 2014) or words (Schacht and Sommer, 2009; Ibáñez et al, 2014). Petroni et al (2011) found that the recognition of face valence is associated to the ability to read others' intentions.…”
Section: Introductionmentioning
confidence: 99%
“…In support to this notion, the recognition of basic features (i.e., perceptual) carrying primary emotional information has been considered a fast and automatic process (Pratto and John, 1991; Öhman et al, 2001) responsible for programing and executing social responses (Fazio and Olson, 2003). This view has emerged from the use of experimental tasks designed to evaluate emotion recognition of faces (Heuer et al, 2007; Hurtado et al, 2009; Luo et al, 2010; Ibáñez et al, 2011, 2014; Petroni et al, 2011; Zhang et al, 2014) or words (Schacht and Sommer, 2009; Ibáñez et al, 2014). Petroni et al (2011) found that the recognition of face valence is associated to the ability to read others' intentions.…”
Section: Introductionmentioning
confidence: 99%
“…The way in which individuals interpret face and perform facework varies among cultures and contexts ; consequently, facework conflict styles are contingent on cultural, situational, and individual factors (Zhang et al, 2014). Given the demand for Western expatriate hotel managers in China, and considering the dichotomous nature of Eastern and Western cultures, it would be of benefit to multinational hotel firms to promote a cross-cultural understanding among expatriate mangers with regard to their Chinese subordinate employees.…”
Section: Resultsmentioning
confidence: 99%
“…In Chinese culture, face maintains far-reaching implications in relationships with peers, families, and coworkers (Leung, Chen, Zhou, & Lim, 2011). In the literature, two types of face have been identified, self-face and other-face, both referring to styles of behaviors in Face Negotiation Theory (Zhang, Ting-Toomey, & Oetzel, 2014).…”
Section: Facementioning
confidence: 99%
See 1 more Smart Citation
“…While conflict styles are subject to the interplay of cultural, situational, and individual variables, by and large, culture exerts a strong influence on people's conflict style preferences and selection (Cai & Fink, 2002;Ting-Toomey, 2005;Zhang, Ting-Toomey, & Oetzel, 2014). In spite of some minor inconsistencies, studies demonstrate that members from individualistic cultures tend Communication Quarterly 3 to be more competing and confrontational, but less avoiding and obliging, than those from collectivistic cultures (Croucher et al, 2012;Oetzel & Ting-Toomey, 2003;Oetzel et al, 2001;Ting-Toomey, 2005).…”
Section: Cultural Influences On Conflict Stylesmentioning
confidence: 99%